SISTEM INFORMASI MANAJEMEN DISTRIBUSI (STUDI KASUS : PT ARDERAMA MANDIRI) - Dani Pradana Kartaputra; Herna Gunawan; Naifal Shidqi Kurniawan (LPPM STMIK BANDUNG, 2022)
PT. Arderama Mandiri is a company engaged in distributors and importers,distributing printed goods, office equipment, musical instruments, computer fittings and software, etc. The delivery of goods has become more widespreadin 2011. At this time the company is increasingly showing an increase, namely the increasing number of consumers who order goods, the increase achieved sometimes even causes problems such as the number of consumerswho complain because of long delivery times, the warehouse department has difficulty monitoring the delivery of goods to consumers. Reflecting on this problem, it is necessary to build a system that can monitor the distribution ofgoods effectively. Website- based Distribution Management Information System is an information system built using the waterfall Software Development Life Cycle (SDLC) method which has 6 stages including System Engineering, Analysis,Design, Coding, Testing and Maintenance. This method is done by looking atand analyzing the problem using the Unified Modeling Language (UML). Then design a solution in the form of a wireframe website for an informationsystem, if it's finished then go to the Coding stage or build a system using the PHP programming language and the Laravel framework